Student’s Perceptions Towards Mobile Technology in Distance Learning At 2nd Semester in English Language Education Program - Amien Rahman; Widi Syahtia Pane; Abdul Rohman (Inquest Journal, 2023)
Background: Mobile learning is a learning model by utilizing information and communication technology. One form of technology that can be used in mobile learning is smartphones. There is a wide variety of smartphones that offer incredible sophistication in various features and applications. With various features that can be installed or run online, smartphones can be used as learning media. Methodology: This study used a qualitative approach and a case study as the research design. Moreover, the researcher used interviews and observation as the instrument to collect the data. The subjects in this study are five students. Findings: The findings revealed positive perceptions and the obstacles of mobile learning in Distance Learning. The results of this study stated that the subjects were greatly helped by the presence of mobile learning. Mobile learning is very helpful for subjects to find information and communication with easy internet access in finding information during a pandemic helping students find and gather information. it was stated that with mobile learning students had the flexibility of place. However, the obstacle to mobile learning in distance learning is students cannot directly understand the material presented by the lecturer. Apart from that, students also find it difficult to understand the material as a result of the poor quality of the unstable internet. Conclusion: There are some students who have obstacles during mobile-based learning. The obstacles that are often faced by students are network constraints that are sometimes less supportive when the teaching and learning process takes place. With this mobile-based learning, students can access smooth communication information without being constrained by place, time, and understanding of the material that can be accessed by students independently. Originality: In this study found out the students’ perception and the obstacles used PJJ or distance learning with use mobile technology in learning process.